INTERVENTIONS TARGETING IMPAIRED FASTING GLUCOSE: A COMPREHENSIVE REVIEW OF STRATEGIES TO PREVENT TYPE 2 DIABETES - Marzena Swojnóg; Zuzanna Dobrakowska; Radosław Swędrak; Jakub Klepacz (International Journal of Innovative Technologies in Social Science, 2026)
Objective: Impaired Fasting Glucose (IFG), a state of prediabetes characterized by elevated fasting glucose levels, signifies a significantly increased risk of developing Type 2 Diabetes Mellitus (T2D) and associated cardiovascular complications. This comprehensive review systematically analyzes evidence from original research, including Randomized Controlled Trials (RCTs), prospective and retrospective cohort studies, and single- and multi-center implementation experiences, to evaluate the effectiveness and translation challenges of interventions targeting IFG progression.Methods: A targeted literature search was conducted across major medical databases, focusing on human intervention studies published between 2000 and 2025. Included articles were categorized based on intervention type (Intensive Lifestyle Intervention [ILI] or pharmacological) and study design, with an emphasis on T2D incidence rate reduction as the primary outcome.Key Findings: The analysis confirms that ILI, focused on diet, physical activity, and achieving moderate weight loss (5–7%), remains the most efficacious long-term strategy, demonstrating superior and sustained T2D risk reduction (e.g., 58% in the Diabetes Prevention Program) (Diabetes Prevention Program Research Group, 2002); (Tuomilehto et al., 2001). Metformin therapy serves as a critical, cost-effective pharmacological alternative, particularly for high-risk subgroups (e.g., younger individuals, high BMI). Translational studies, including retrospective and multi-center experiences, highlight significant barriers to real-world implementation, such as low sustained adherence and scalability challenges within diverse populations.Conclusion: Effective T2D prevention in individuals with IFG necessitates early, risk-stratified intervention. While ILI is the gold standard, future strategies must focus on developing tailored, technologically-supported, and scalable programs to overcome implementation barriers and maximize population-level health impact.